Disguised Foreign Controlled Companies and the Facilitation of Transnational Criminal Activities in Thailand - Chokprajakchat, Srisombat; Techagaisiyavanit, Wanaporn; Iyavarakul, Tongyai; SiripornYamnill; Bunnag, Theerat; Narongsak, Tunlawat (International Journal of Criminology and Sociology, 2021)
The primary objectives of the study are to examine the role of a business using Thai nationals as nominee shareholders in foreign-controlled companies in the facilitation of the transnational criminal groups’ activities in the tourist destinations, and their social and economic impacts on the country. Nominee shareholder appointment in a legal entity has commonly been recognized as one of the techniques employed by criminal groups to launder and obscure the ownership of their illegal assets. However, this study points out that this type of company also performs other functions in providing resources and a platform for criminal groups to further their goals. The study used mixed methods by gathering qualitative data through conducting in-depth interviews and focus groups with 55 participants from relevant government agencies and private sectors, and by gathering quantitative data through conducting public surveys consisting of 1,160 participants from six provinces across five different regions in Thailand. The study concluded that there is a strong need for the country to improve monitoring mechanisms through legal changes, and collaborations among public, private and civil society as the practice of nominee shareholder appointment, although perceived as a normal practice in the global field of business, such a practice can invite unintended consequences, which can be a serious cause of concern due to the links with illegal activities operated under the umbrella of transnational organized crime.